A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China - Volynkin, Anton V.; Gyulai, Péter (Zootaxa, 2018)
The genus Athaumasta Hampson, 1906 is a small genus of the subfamily Bryophilinae, distributed from Central Asia through mountains of South Siberia to the Korean Peninsula. It is closely related to the genera Victrix Staudinger and Bryophila Treitschke, but differs in forewing pattern, strong pectination of the male antennae, a narrow and dorso-laterally flattened uncus, and distally narrowed and apically pointed male valves. The taxonomy of the genus was discussed by Volynkin & Pekarsky (2016). At present the genus includes 10 valid species, some of which were described recently (Volynkin 2012; Volynkin & Pekarsky 2016; Pekarsky 2017), and several taxa await description (Kononenko 2016). The present paper describes a new Athaumasta species from southwestern Mongolia and north-western China related to A. pekarskyi Volynkin, 2012.